The Influence Of Prayer On The Morals Of Muslim Adolescents In The Perspective Of Surat Al-Ankabut Verse 45 - Pertiwi, Anggi Amelia; Ali, Zaky Mumtaz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
Prayer plays an important role in shaping noble morals, as explained in the Qur’an. But, today’s teenagers face many challenges in the form of moral crises, evident from the rising cases of juvenile delinquency, some even leading to criminal acts. This shows that not all Muslim teenagers are able to reflect the values of prayer in their morals. This research aims to analyze the interpretation of Surah Al-Ankabut verse 45, which discusses the influence of prayer in preventing immoral and evil acts, and to measure how prayer influences the character if adolescents. This research uses a mixed method approach, combining qualitative and quantitative approaches. The qualitative method is applied through the analysis of qur’anic interpretation using Analytical Exegesis (Al-Tafsir al-Tahlili) while the quantitative method is used to analyze numerical data using SPSS software. The research presents two main findings. First, according to the Qur’anic Exegetes, prayer effective in preventing immoral and wicked deeds must encompass three aspects: Fi‘liyah (implementation), Qauliyah (recitation), Qalbiyah (heart contemplation). Second, the quantitative analysis shows that prayer has a significant influence on students' morals, contributing 14,9%. These findings emphasize the importance of deep understanding and correct implementation of prayer in shaping good character among students. The novelty of this research is in its holistic approach to the practice of prayer, which not only measures the frequency of prayer but also assesses student understanding of prayer and the noble values contained in its practice.